The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0100-40422012000400016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pesticide adsorption in gas chromatographic injector and column

Abstract: Components in complex matrices can cause variations in chromatographic response during analysis of pesticides by gas chromatography. These variations are related to the competition between analytes and matrix components for adsorption sites in the chromatographic system. The capacity of the pesticides chlorpyrifos and deltamethrin to be adsorbed in the injector and chromatographic column was evaluated by constructing three isotherms and changing the column heating rate to 10 and 30 ºC min-1. By using ANCOVA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has been shown that the intensity of this effect is dependent on the physicochemical properties of pesticides such as polarity, molecular weight, thermal stability, temperature of boiling analytes, etc. 29,30 Negative matrix effect is observed due to degradation of the pesticide in injector or analyte adsorption on the active sites (free silanols groups) from liner. This effect causes decreasing of the analyte flux transferred to the column and consequently the decreasing of the detector signal.…”
Section: Matrix Effect and Linearitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the intensity of this effect is dependent on the physicochemical properties of pesticides such as polarity, molecular weight, thermal stability, temperature of boiling analytes, etc. 29,30 Negative matrix effect is observed due to degradation of the pesticide in injector or analyte adsorption on the active sites (free silanols groups) from liner. This effect causes decreasing of the analyte flux transferred to the column and consequently the decreasing of the detector signal.…”
Section: Matrix Effect and Linearitymentioning
confidence: 99%
“…31 When the sample matrix is injected, there is a competitive process between the analyte and other matrix compounds to be adsorbed on liner active sites, which favors the analyte availability to the column and consequently bring an increase of the signal. [29][30][31] Thus, the comparative responses between the analyte presented in the standard solution and in the sample matrix are characterized by an response overestimation. Probably these discussed aspects justify the positive matrix effect observed for most pesticides studied, except for dichlorvos (Figure 2a).…”
Section: Matrix Effect and Linearitymentioning
confidence: 99%
“…On the other hand, even though it is not fully recognized, there is limited evidence that coexisting pesticides in standard solutions have the potential to cause response alterations for certain other pesticides. de Pinho et al compared the adsorption tendency of chlorpyrifos and deltamethrin in GC with an electron capture detector and found that deltamethrin adsorbed much more readily to the active sites than chlorpyrifos [24]. They also found that deltamethrin acted as a sort of analyte protectant for chlorpyrifos and altered its peak response when both pesticides were mixed and injected to GC with an electron capture detector.…”
Section: Introductionmentioning
confidence: 99%
“…de Pinho et al. compared the adsorption tendency of chlorpyrifos and deltamethrin in GC with an electron capture detector and found that deltamethrin adsorbed much more readily to the active sites than chlorpyrifos . They also found that deltamethrin acted as a sort of analyte protectant for chlorpyrifos and altered its peak response when both pesticides were mixed and injected to GC with an electron capture detector.…”
Section: Introductionmentioning
confidence: 99%